A bibliometric study of digital health campaign strategies, effectiveness, and trends (2015-2023) - Febrian Gibran Juliansyah; Anwar, Rully Khairul (Faculty of Communications Science, Dr. Soetomo University, 2025)
This study employed a bibliometric approach to analyse research trends in health communication campaigns in the digital era from 2015 to 2023. Focusing on specific search criteria, a dataset of 64 scholarly articles was extracted and analysed to understand the development of scientific publications in health communication campaigns. The bibliometric analysis provides insights into the citation trends and collaborations between authors and institutions on the discussed topics. This study incorporates thematic analysis to understand the context of digital communication content in health campaigns. Using Biblioshiny software and Google Spreadsheets, the bibliometric data is presented to offer a comprehensive overview of the research topic. This analysis identifies significant publication growth, highlighting influential authors, journals, countries, and maps core thematic areas such as the role of social media in health information dissemination. These findings offer data-driven perspectives for developing more effective digital communication strategies in the context of public health.